Expression and localisation of vascular ribonucleases in endothelial cells - Fischer, Silvia; Nishio, Miwako; Dadkhahi, Sara; Gansler, Julia; Saffarzadeh, Mona; Shibamiyama, Aya; Kral, Nicolé; Baal, Nelli; Koyama, Takatoshi; Deindl, Elisabeth; Preissner, Klaus T. (Thrombosis and Haemostasis, 2011)
The functions of extracellular RNA in the vascular system as new procoagulatory and permeability-increasing factor in vivoand in vitrowere shown to be counteracted by pancreatic type RNase1. Based on the identification of RNase1 in plasma and serum, it is proposed that the enzyme is expressed by vascular cells to contribute in the regulation of extracellular RNA. It is demonstrated that RNase1 and RNase5 (also termed angiogenin) were differentially expressed in various types of endothelial cells, whereby human umbilical vein endothelial cells (HUVEC) expressed and released the highest concentration of active RNase1. Expression and release of RNase5 were similar in all types of endothelial cells tested. Both RNases were constitutively produced and secreted, whereby a portion of RNase1, but not RNase5, was stored in Weibel-Palade bodies, co-localising with von Willlebrand factor and P-selectin. Accordingly, immediate release of RNase1 from these granules was demonstrated in vitroand in vivousing Weibel-Palade body exocytosis-inducing agents. Additionally, extracellular RNA or poly:IC (but not DNA) induced this short-term release of RNase1. Our results indicate that vascular RNase1 and RNase5 are mainly produced by vascular endothelial cells and can serve, depending on the vascular bed, different functions in vascular homeostasis and endothelial cell responses.
Keywords: Human pancreatic RNase1; angiogenin; endothelial cells; WeibelPalade bodies